2010
DOI: 10.1136/emj.2009.087486
|View full text |Cite
|
Sign up to set email alerts
|

Is it the H or the EMS in HEMS that has an impact on trauma patient mortality? A systematic review of the evidence

Abstract: Background and aim Prehospital care of trauma patients is a matter of great debate. The optimal transport method remains undecided, with conflicting data comparing helicopter and ground emergency medical transfer. This study systematically reviews the evidence comparing helicopter and ground transfer of trauma patients from the scene of injury. Methods A systematic literature review of all population-based studies evaluating the impact on mortality of helicopter transfer of trauma patients from the scene of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 54 publications
2
79
0
3
Order By: Relevance
“…[2] When comparing the mean on-scene times of both the Netcare 911 HEMS operations with other similarly staffed operations, the mean on-scene times for the Netcare operations were often shorter. [7,20,21] An interesting finding was the similarity between the interfacility transfer and primary transfer on-scene times. The transfer times from scene to hospital for both the Netcare 911 HEMS operations were similar to another SA study.…”
Section: Discussionmentioning
confidence: 94%
“…[2] When comparing the mean on-scene times of both the Netcare 911 HEMS operations with other similarly staffed operations, the mean on-scene times for the Netcare operations were often shorter. [7,20,21] An interesting finding was the similarity between the interfacility transfer and primary transfer on-scene times. The transfer times from scene to hospital for both the Netcare 911 HEMS operations were similar to another SA study.…”
Section: Discussionmentioning
confidence: 94%
“…16 The feasibility and demand of air ambulance medical service is also worth of consideration. 17 An Australian study has shown that if the distance of EMS is in the range of 100 km with accessible land traffic, there is no apparent advantage of using the air ambulance transport to improve time to definite care. 18 In our study, the mean distance from the fire station to the most nearby hospital was 34.5 km.…”
Section: Discussionmentioning
confidence: 99%
“…Applying liberal policy for the use of civil helicopters to transport patients failed to demonstrate clear benefits [13,14]. On the other hand, a number of reports have provided evidence of positive impact in patients' outcomes [15][16][17]. Some investigators advocated that helicopter evacuations have a considerable influence on the survival of the more severely injured patients but does not demonstrate significant impact on the less injured [16].…”
Section: Managementmentioning
confidence: 99%